2018
DOI: 10.1186/s12862-018-1247-5
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal variation among populations of a fungus-farming ant: implications for karyotype evolution and potential restriction to gene flow

Abstract: BackgroundIntraspecific variation in chromosome structure may cause genetic incompatibilities and thus provides the first step in the formation of species. In ants, chromosome number varies tremendously from 2n = 2 to 2n = 120, and several studies have revealed considerable variation in karyotype within species. However, most previous studies were limited to the description of chromosome number and morphology, and more detailed karyomorphometric analyses may reveal additional, substantial variation. Here, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Establishment of the karyotype (the chromosome number and determination of their morphology) is very important for the knowledge of chromosomal variations and possible genetic barriers between phylogenetic groups (Cristiano et al 2017;Cardoso et al 2018b). It is necessary to go further in describing the chromosome number and morphology, as more detailed karyomorphometric analyses may reveal additional and substantial variations not observed previously, mainly when accompanied with genome size estimates (Cardoso et al 2018b). Tsutsui et al (2008) state that closely related species, belonging to the same genus, may have very similar genome sizes, corroborating the pattern revealed by our karyomorphometric analyses in the Acromyrmex species studied here.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Establishment of the karyotype (the chromosome number and determination of their morphology) is very important for the knowledge of chromosomal variations and possible genetic barriers between phylogenetic groups (Cristiano et al 2017;Cardoso et al 2018b). It is necessary to go further in describing the chromosome number and morphology, as more detailed karyomorphometric analyses may reveal additional and substantial variations not observed previously, mainly when accompanied with genome size estimates (Cardoso et al 2018b). Tsutsui et al (2008) state that closely related species, belonging to the same genus, may have very similar genome sizes, corroborating the pattern revealed by our karyomorphometric analyses in the Acromyrmex species studied here.…”
Section: Resultsmentioning
confidence: 99%
“…striatus (Cristiano et al 2013). Such chromosomal features are essential for understanding chromosomal variants and the possible genetic barriers among phylogenetic groups (Cardoso et al 2018b). Ac.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we demonstrated once again that differences in karyotype length can represent the variation in the estimates of genome size in either the cytotypes or among populations. In a study of geographically distant populations of the fungus-farming ant Mycetomoellerius holmgreni Cardoso et al [16] suggested that the correlation between genome size and karyotype length is probably due to changes in the centromeric satellite DNA. They also hypothesized that the changes in the karyotypes of the study populations are molded by a process of centromere drive, which favors the evolution of the karyotype and acts as a potential barrier to gene flow.…”
Section: Plos Onementioning
confidence: 99%
“…A number of studies have shown that genome size varies considerably among species and even between closely-related taxa [49], although only a few studies have focused on, and quantified, the extent of the variation in genome size among populations [16,50]. Some ecological and physiological traits have been correlated with the size of the genome, e.g., metabolic rate, genome expression, and cell size [3], and all these traits have a direct effect on the fitness of the organism, and are thus subject to natural selection [51].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation